Comparing Biorefinery Processes at the Early Design Stage Using Large Block Analysis - Trottier, Émanuelle; Myers, Craig; Stuart, Paul (Frontiers in Sustainability, 2022)
The transformation of pulp and paper mills through the integration of biorefineries is increasingly considered essential to the future of many existing sites. However, evaluating the risk and return of different biorefinery process alternatives at the early design stage is challenging. There are many strategies and technologies that must be considered, each of which is typically accompanied by its unique risks, including high levels of uncertainty in capital and operating cost estimates often obtained from technology providers. The novel methodology presented in this study, called Large Block Analysis (LBA), comprises a systematic approach for addressing these important challenges at the early design stage. LBA is used to obtain relative cost estimates for six process/product combinations incorporating different Technology Readiness Levels (TRLs), for adding value to a hemicellulose stream extracted from hardwood chips. In this case study, it was found that the fixed capital costs obtained using the LBA method differed from the original costs by between 121 and −19%, and operating cost estimates differed by between 117 and −17% from the original. The results show that the most economically-viable options for the hemicellulose stream having reasonable technology risk included the production of (1) animal feed additives, (2) xylitol using a variant of the classical chemical process, and (3) furfural.